Effects of Driving ForceEnergy(∆V)^° (eV) on the Rates of Electron-Transfer Reactions at Metal/LiquidInterface - Hadi, J.M. AL-Agealy; Waleed Bdaiwi Salih; Taif, S. Murdhi (Journal of Madenat Alelem University College, 2013)
Electron transfer (ET) in metal/liquid interface exhibits dependence on the driving free-energy〖∆V〗^°. It has been studied depending on the quantum theory. The driving force energies 〖∆V〗^° for the electron transfer reaction are calculated as a function of the reorganization E_met^liq, and absorption energy E_abswhen a light is incident on the donor-acceptor system. The results show that the driving force energy 〖∆V〗^°for electrons increase with increases absorption energy and decreasing with wave length and reorganization energyE_met^liq. A MATLAP program has been used to calculate the reorganization energyE_met^liq, driving free energy〖∆V〗^°, and the rate constant of electron transferR_ET. The present results show that the rate constant R_ETincreases with the increasing of the reorganization energy E_met^liq, and with the decreasing of the driving force energy〖∆V〗^°. Probability of electron transfer occurs in most polar solvent f(n,ε) system and has low driving force energy.